2020
DOI: 10.3390/cancers12102883
|View full text |Cite
|
Sign up to set email alerts
|

Novel Treatment Strategies for Glioblastoma

Abstract: Glioblastoma (GBM) is the most common primary central nervous system tumor in adults. It is a highly invasive disease, making it difficult to achieve a complete surgical resection, resulting in poor prognosis with a median survival of 12–15 months after diagnosis, and less than 5% of patients survive more than 5 years. Surgical, instrument technology, diagnostic and radio/chemotherapeutic strategies have slowly evolved over time, but this has not translated into significant increases in patient survival. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 85 publications
1
52
0
Order By: Relevance
“…The median survival time of GBM patients is approximately 12-15 months. 2 Reprogramming of energy metabolism is an important indicator of malignant tumors. [3][4][5] Abnormal energy metabolism has also been reported in GBM and includes enhanced aerobic glycolysis and lipid synthesis to provide energy and raw materials to the highly proliferating cells.…”
Section: Glioblastoma As a Major Medical Challengementioning
confidence: 99%
“…The median survival time of GBM patients is approximately 12-15 months. 2 Reprogramming of energy metabolism is an important indicator of malignant tumors. [3][4][5] Abnormal energy metabolism has also been reported in GBM and includes enhanced aerobic glycolysis and lipid synthesis to provide energy and raw materials to the highly proliferating cells.…”
Section: Glioblastoma As a Major Medical Challengementioning
confidence: 99%
“…Malignant gliomas that originate from glial, neural stem cells and astrocytes are the most aggressive tumors of the central nervous system (CNS) and spinal cord with a median survival of less than 12–15 months [ 1 ]. The current standard of care therapies such as surgery, radiotherapy, and chemotherapy have had only limited success in increasing the lifespan of glioma patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A safe maximal excision of the glioma without neurological functioning de ciency was the main therapeutic strategy as strong evidence has demonstrated that more extensive resections can prolong patients' survival time [6,27,28]. Both the OS and CSS nomograms in the study showed that surgery was a strong individual predictive factor for LGGs and gross total resection (GTR) is recommended under permissive conditions.…”
Section: According To Our Nomograms Age At Diagnosis Was Con Rmed Asmentioning
confidence: 92%